Spiritual beliefs, practices, and needs at the end of life: Results from a New Zealand national hospice study. Issue 2 (30th August 2016) - Egan, Richard; MacLeod, Rod; Jaye, Chrystal; McGee, Rob; Baxter, Joanne; Herbison, Peter; Wood, Sarah
Abstract: Objective: International studies have shown that patients want their spiritual needs attended to at the end of life. The present authors developed a project to investigate people's understanding of spirituality and spiritual care practices in New Zealand (NZ) hospices. Method: A mixed-methods approach included 52 semistructured interviews and a survey of 642 patients, family members, and staff from 25 (78%) of NZ's hospices. We employed a generic qualitative design and analysis to capture the experiences and understandings of participants' spirituality and spiritual care, while a cross-sectional survey yielded population level information. Results: Our findings suggest that spirituality is broadly understood and considered important for all three of the populations studied. The patient and family populations had high spiritual needs that included a search for (1) meaning, (2) peace of mind, and (3) a degree of certainty in an uncertain world. The healthcare professionals in the hospices surveyed seldom explicitly met the needs of patients and families. Staff had spiritual needs, but organizational support was sometimes lacking in attending to these needs. Significance of results: As a result of our study, which was the first nationwide study in NZ to examine spirituality in hospice care, Hospice New Zealand has developed a spirituality professional development program. Given that spirituality was found to be important to the majority of our participants, it is hoped that the adoption of such an approach will impact on spiritual care for patients and families in NZ hospices.